The new radical right as a challenge to governance and the democracy´s quality - Lerín Ibarra, David (Cuadernos de Gobierno y Administración Pública, 2019)
The electoral growing and consolidation of radical new right political organizations, in the last decades, represents a challenge for the quality of Western democracy. This phenomenon has spread by practically all Europe, undermining the progress already done in the construction of multicultural and cosmopolitan societies, therefore endangering their social diversity. In this article of a theoretical nature, we have as objective the conceptualization of these formations, distinguishing the extreme right from the new radical right through a comparative analysis between both currents. In this way and following this methodology, we will analyze two ideological principles of these parties that pose a risk for democratic governance: defense of the ethnic nation and the palingenetic ultranationalism.